The over-the-scope grasper (OTSG) - Brand, Markus; Hofmann, Nico; Ho, Chi-Nghia; Meining, Alexander (Endoscopy, 2020)
Background Endoscopic removal of foreign bodies, coagulated blood, or necrotic debris is sometimes challenging and time-consuming, partly because of inadequate endoscopic instruments. Therefore, new devices are needed to overcome the current limitations.Methods The over-the-scope grasper (OTSG) is a new grasping tool that can be attached to any standard gastroscope. It has been developed for endoscopic removal of larger particles. We present retrospective data on five patients who were treated using the device for various indications, including necrosectomy, bolus impaction, and removal of blood clots.Results In two patients, the OTSG was used through a lumen-apposing metal stent for direct endoscopic necrosectomy after severe pancreatitis. The other patients had a massive blood clot in the esophagus after endoscopic submucosal dissection, or aphagia due to large meat chunks clogging the esophagus. The OTSG was used with technical success in all of the patients and without any procedure-associated complications.Conclusion The OTSG appears to be a useful device for endoscopic removal of larger particles, blood clots, or necrotic debris. Preliminary experience shows that the device is effective and easy to use.